RELIGION, IDENTITY POLITICS AND PARLIAMENTARY ELECTIONS IN INDIA - Djogatovic, Veljko (Political Review, 2025)
This paper analyses the religious identity politics that shaped the 2024 general elections in India. In a country with vast ethnic, religious, and cultural differences, identity politics play a key role in political life, as political parties mobilize voters by appealing to national, religious, ethnic, and regional/local identities. The research focuses on how identity politics was used by dominant political actors, such as the Bharatiya Janata Party (BJP) and the Indian National Congress (INC), as well as smaller parties and social movements. The paper analyses how different groups became central to political strategies during the election campaign and how identity-based mobilization influenced the election results. In conclusion, the paper explores the long-term consequences of these policies on social cohesion and the democratic process in India, as well as on the state of secular legal, political, and social order.
Keywords: identity politics; India; parliamentary elections; religion; politics; Bharatiya Janata Party; secularism; Hindutva; Hinduism